MEDIA POP-UP SEBAGAI SARANA MENINGKATKAN INTERAKSI DAN KOMUNIKASI ANAK TK - Aisyah; Mudhar; Latifah, Magfirotul; Hartanti, Jahju; Hasiana, Isabella; Dia Eka Wati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the effectiveness of pop-up media in improving interaction and communication skills of kindergarten B students. The problem underlying this research is the low level of children’s verbal interaction and communication skills during classroom learning activities. This study employed a quantitative experimental method using a pretest–posttest control group design. The participants were 16 kindergarten students divided into an experimental group and a control group. The experimental group was taught using pop-up media, while the control group received conventional instruction. Data were collected through observation sheets and performance tests, and were analyzed using the Wilcoxon Signed Ranks Test. The results showed that the significance values were 0.012 and 0.011, which are lower than 0.05, indicating a significant difference between pretest and posttest scores. These findings demonstrate that the use of pop-up media has a significant positive effect on improving children’s interaction and communication skills. Therefore, pop-up media can be considered an effective and engaging learning medium to support language and communication development in early childhood education.